Chem Differential Eq HW Solutions Fall 2011 193

Chem Differential Eq HW Solutions Fall 2011 193 - a = 0 and...

This preview shows page 1. Sign up to view the full content.

Section A.5 The Power Series Method, Part II A193 So y ±± +2 xy ± + y = 0 implies that ( m + 2)( m +1) a m +2 +(2 m +1) a m =0 a m +2 = - (2 m +1) ( m + 2)( m +1) a m for all m 0 . So a 0 and a 1 are arbitrary; a 2 = - 1 2 a 0 , a 4 = - 5 4 · 3 a 2 = 5 4! a 0 , a 6 = - 9 6 · 5 5 4! a 0 = - 9 · 5 6! a 0 , . . . a 3 = - 3 3 · 2 a 1 a 5 = - 7 5 · 4 a 3 = 7 · 3 5! a 1 a 7 = - 11 · 7 · 3 7! a 1 . . . So y = a 0 ± 1 - 1 2 x 2 + 5 4! x 4 - 9 · 5 6! x 6 + ··· ² + a 1 ± x - 3 3! x 3 + 7 · 3 5! x 5 - 11 · 7 · 3 7! x 7 + ··· ² . 13. To solve (1 - x 2 ) y ±± - 2 xy ± +2 y =0 , y (0) = 0, y ± (0) = 3, follow the steps in Example 5 and you will arrive at the recurrence relation a m +2 = m ( m +1) - 2 ( m + 2)( m +1) a m = ( m + 2)( m - 1) ( m + 2)( m +1) a m = m - 1 m +1 a m ,m 0 . The initial conditions give you
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: a = 0 and a 1 = 3. So a 2 = a 4 = ··· = 0 and, from the recurrence relation with m = 1, a 3 = (1-1 1 + 1 a = 0 . So a 5 = a 7 = ··· = 0 and hence y = 3 x is the solution. 17. Put the equation (1-x 2 ) y ±±-2 xy ± + 2 y = 0 in the form y ±±-2 x 1-x 2 + 2 1-x 2 y = 0 ....
View Full Document

This note was uploaded on 12/22/2011 for the course MAP 3305 taught by Professor Stuartchalk during the Fall '11 term at UNF.

Ask a homework question - tutors are online